Penegakan Hukum terhadap Tindak Pidana Judi Online oleh Ditreskrimsus Polda Jawa Timur (Studi Kasus Putusan Nomor 475/Pid.B/2026/PN Sby) - Moch Abdan Salam; Singgih Januratmoko; Zainal Arifin Hossein (Yayasan Kawanad, 2026)
This study aims to analyze law enforcement against online gambling offenses by the Special Criminal Investigation Directorate (Ditreskrimsus) of the East Java Regional Police, identify the obstacles encountered, and examine the application of law in Decision Number 475/Pid.B/2026/PN Sby based on criminal law provisions and the Electronic Information and Transactions Law (ITE Law). This study employs an empirical legal research method with an empirical juridical approach. The data were analyzed qualitatively to examine the implementation of law enforcement and the application of legal provisions to online gambling offenses. The results show that law enforcement against online gambling offenses is carried out through pre-investigation, investigation, collection and examination of electronic evidence, and the imposition of criminal sanctions on perpetrators based on applicable legal provisions. The implementation of law enforcement still faces several obstacles, including difficulties in tracing perpetrators, proving offenses through electronic evidence, limited facilities and human resources, and low public legal awareness. Meanwhile, the application of law in Decision Number 475/Pid.B/2026/PN Sby shows that the gambling offense committed through electronic media was processed through the criminal justice system and resulted in the imposition of a criminal sentence on the defendant. The decision demonstrates the application of criminal law enforcement to technology-based gambling offenses in order to provide legal certainty and maintain public order.